2016
DOI: 10.1002/pbc.25971
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Multiyear Control of Relapsed T‐Cell Acute Lymphoblastic Leukemia With Successive Donor Lymphocyte Infusions: A Case Report

Abstract: There are few therapeutic options for patients with T-ALL who have recurrent disease after initial matched sibling hematopoietic stem cell transplantation. While a second HSCT from a haploidentical donor offers the conceptual possibility of greater graft-vs-leukemia effect, there is minimal literature to describe the efficacy of this approach in recurrent pediatric T-ALL. We present the case of a now 9 year old girl in whom second haploidentical HSCT, followed by successive donor lymphocyte infusions (DLI) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…These results indicate that using DLI to eradicate residual leukemic clones in T-ALL patient after HSCT is quiet useful and helpful for prolonging the survival of patients and preventing leukemia recurrence. Allen et al reported similar results in a study in which DLI successfully controlled MRD and led to a disease-free survival of more than 3 years for a 9-year-old T-ALL patient [11]. These results indicate that DLI may be used as a common strategy for T-ALL patients with MRD after HSCT.…”
Section: Discussionmentioning
confidence: 63%
“…These results indicate that using DLI to eradicate residual leukemic clones in T-ALL patient after HSCT is quiet useful and helpful for prolonging the survival of patients and preventing leukemia recurrence. Allen et al reported similar results in a study in which DLI successfully controlled MRD and led to a disease-free survival of more than 3 years for a 9-year-old T-ALL patient [11]. These results indicate that DLI may be used as a common strategy for T-ALL patients with MRD after HSCT.…”
Section: Discussionmentioning
confidence: 63%
“…From this limited published literature, it appears that in contrast to AML, in which non-targeted adoptive cell therapies with DLI or NK cells can produce significant benefit, similar approaches in T-ALL had only modest effects. While in rare instances patients with refractory or relapsed T-ALL responded to DLI (alone or in combination with chemotherapy) 33,34 , in most patients the efficacy of such non-specific cell therapy approaches was limited, highlighting the need for more effective targeted cell therapy options.…”
Section: C1 Dlis Tcr-and Nk-based Therapies For T-allmentioning
confidence: 99%